Rapid and Simple Determination of Nitrite in Soil by Using Portable and Miniaturized Electrochemical Tools - Maria-Lorena Jinga; Lucian-Gabriel Zamfir; Petru Epure; Mariana Constantin; Iuliana Răut; Maria-Luiza Jecu; Mihaela Doni; Ana-Maria Gurban (Proceedings)
Nowadays, the rapid and easy determination of nitrite in the environment and foods represents a necessity since its chemical importance has been highlighted in many fields, especially in food and agriculture development [...]